Pengembangan Lembar Kerja Peserta Didik Pada Materi Virus Untuk Kelas X SMA/MA - Santi, Amelia; Nerita, Siska; Zural, Mimin Mardhiah (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The use of appropriate teaching materials is a very important factor in improving students' ability to understand a lesson. However, there are still lessons that use LKPD which only contain a collection of questions, so they are not able to increase student activity in learning activities. Therefore, teaching materials such as LKPD are needed that can meet students' needs. The aim of this research is to create an LKPD accompanied by practice questions on Class X SMA/MA virus material that is valid and practical. This type of research is research and development with a 4D development model. At the development stage, validation is carried out by validators and questionnaires regarding readability and practicality are given to teachers and students. The research instruments used were validity questionnaires, readability questionnaires and practicality questionnaires. The results of the study showed that the resulting LKPD has very valid criteria with a validity score of 95.66%, very readable with a readability score of 96.69% and very practical with practicality scores obtained from teachers and students of 90.19% and 94, respectively. 47%. Thus it can be concluded that the LKPD developed can be used in learning.